Palladium Grafted Functionalized Nanomaterial: An Efficient Catalyst for the CO2 Fixation of Amines and Production of Organic Carbamates. Issue 13 (8th April 2019) - Ghosh, Swarbhanu; Ghosh, Aniruddha; Biswas, Surajit; Sengupta, Manideepa; Roy, Dipanwita; Islam, Sk. Manirul
Abstract: Chemical fixation of carbon dioxide through suitable catalytic pathways is very demanding in the context of sustainable environment. An environmentally benign synthetic studies of N‐ formylated amine derivatives by carbon dioxide fixation of amines have been investigated in presence of Merrifield resin supported palladium nanomaterial (Pd‐PS‐amtp catalyst) at ambient temperature. Poly(methylhydrosiloxane) was employed as a susceptible hydride transferring agent in the present CO2 fixation reaction. Further this catalyst exhibited an extended catalytic activity for the production of organic carbamates from dimethyl carbonate and aromatic amines. The Pd‐PS‐amtp nanomaterial has been produced by two step strategies and systematically characterized by FTIR, UV‐ Vis, FE‐ SEM and TGA‐ DTA analysis. The benefits of this system are quite economical, high recycling efficiency and consuming short reaction time to allow significant product yield. The production of organic carbamates in presence of the present catalyst is a phosgene‐ free procedure where dimethyl carbonate (DMC) is utilized both as carboxylating agent and solvent. The recovery of Pd‐PS‐amtp nanomaterial could easily be performed after the reactions and recyclable up to six times without considerable reduction in catalytic activity. Abstract : N‐Formylation of amines via CO2 fixation and production of organic carbamates: An environmentally benign synthetic studies of N‐formylated amine derivatives by carbon dioxide fixation of amines have been investigated in presence of Merrifield resin supported palladium nanomaterial (Pd‐PS‐amtp catalyst) at ambient temperature. The production of organic carbamates in presence of the present catalyst is a phosgene‐free procedure where dimethyl carbonate (DMC) is utilized both as carboxylating agent and solvent.